High-yielding and multiple stress resistance field pea varieties suitable for cultivation in north-eastern plains of India - Parihar, A K; Dixit, G P (Indian Farming, 2024)
Field pea (Pisum sativum L.) is a vital pulse crop in India, particularly in the rabi season, serving as an essential protein source. This article focuses on the development of two new field pea varieties, Shikhar (IPFD 19-1) and Arpan (IPFD 19-3), developed by ICAR-IIPR specifically tailored for the North Eastern Plain Zone (NEPZ). These varieties exhibit high yield potential, disease resistance, and suitability for both irrigated and rainfed conditions. Both varieties exhibit resistance to powdery mildew and ascochyta blight, with moderate resistance to rust, offering improved grain quality. These high-yielding, resilient varieties have the potential to significantly contribute to field pea production in the NEPZ, supporting increased productivity in both irrigated and rainfed environments.